UJI EFEKTIVITAS EKSTRAK DAUN AFRIKA (VERNONIA AMYGDALINA) SEBAGAI LARVASIDA PADA LARVA NYAMUK AEDES AEGYPTI - MALINDA NURIANI HASIBUAN; NUR FADLY (LP2MTBM MAKARIOZ, 2023)
Dengue Hemorrhagic Fever (DBD) is a disease caused by dengue virus through the intermediary of female Aedes aegypti mosquitoes. Insecticides with chemicals are widely used as mosquito exterminators, but from previous research there is insecticide resistance. To reduce the incidence of resistance, many previous studies have made plant-based larvacides with plant-based ingredients. African leaves (Vernonia amygdalina) are plants that live in many tropical climates. African leaves (Vernonia amygdalina) contain alkaloid compounds, flavonoids, steroids, saponins and tannins. To find out the effectiveness of african leaf extract (Vernonia amygdalina) as a larvalide in the larvae of the Aedes aegypti mosquito. This study uses a pure experimental study design with a posttest with control design group design with a sample number of 625 larvae of Aedes aegypti instar III-IV in 5 repetitions. Within 24 hours of treatment the concentration of African leaf extract 5%, 10% and 15% showed 100% mortality of test larvae. In the 24-hour treatment there was no difference in the number of Aedes aegypti between African leaf extract and 1% abate. African leaf extract (Vernonia amygdalina) was effective at concentrations of 5%, 10% and 15% as plant-based larvacide in the larvae of the Aedes aegypti mosquito. It is hoped that further research will be conducted to determine the optimal dose of African leaf extract which can have a larvicidal effect on Aedes aegypti and to find the right treatment time to kill 100% of the test larvae.